POTENSI JENIS SENGON (Falcataria moluccana (MIQ.) BARNEBY & J.W. GRIMES) DIPERBANYAK MELALUI TEKNIK VEGETATIF (STEK) Potency of Sengon ( Falcataria moluccana (MIQ.) BARNEBY & J.W. GRIMES) Propagation Throught Vegetative Technique (Cutting) - Dharmawati F. Djam’an; Kurniawati Purwaka Putri; Danu Danu (Lambung Mangkurat University-Indonesia, 2018)
The sengon plant (Falcataria moluccana (Miq.) Barneby & J.W. Grimes) is the mainstay of community forests, especially in Java. During this time, the seed is used as material for seed production. However, at this time began to find a rust attack puru at the level of seedlings are allegedly carried by seed disease. Therefore, there is a need for other techniques to prevent transmission at the seedling level in the nursery. Vegetative technique is one that can be used to break the path of plant diseases by using healthy ingredients and free from disease. This research is aimed to know the potential of sengon plant to be propagated vegetatively, by cuttings method. The method of cuttings used is shoot cuttings and stem cuttings, and the source of cuttings derived from plants aged 1 and 2 years. The results showed that the highest live percentage was stem cuttings originating from 1 year old plant (34.66%), while the live percentage for stem cuttings originating from 2 year old plants was still very low (3.33%).Keywords: Sengon Plant; Vegetative Propogation; Cutting SourceTanaman sengon (Falcataria moluccana (Miq.) Barneby & J.W. Grimes) merupakan jenis andalan hutan rakyat, khususnya di Pulau Jawa. Selama ini, benih digunakan sebagai bahan untuk produksi bibit. Akan tetapi, saat ini mulai ditemukan serangan karat puru pada tingkat semai yang disinyalir penyakit ini terbawa benih. Oleh karena itu perlu adanya teknik lain untuk mencegah penularan pada tingkat bibit di persemaian. Vegetatif teknik merupakan salah satu yang dapat digunakan untuk memutus jalur penyakit tanaman dengan menggunakan bahan tanaman yang sehat dan bebas dari penyakit. Penelitian ini bertujuan mengetahui potensi tanaman sengon untuk diperbanyak secara vegetative, dengan metode setek. Metode setek yang digunakan adalah setek pucuk dan stek batang, dan sumber bahan stek berasal dari tanaman yang berumur 1 dan 2 tahun. Hasil penelitian menunjukkan bahwa persentase hidup tertinggi adalah pada stek batang yang berasal dari tanaman berumur 1 tahun (34.66%), sedangkan persentase hidup untuk stek batang yang berasal dari tanaman umur 2 tahun masih sangat rendah (3,33%).Kata kunci: Tanaman sengon, perbanyakan vegetative, sumber bahan setek